Cibercultura e subjetividade: uma investigação sobre a identidade em plataformas virtuais de hiperespetacularização do eu - Bello, Cíntia Dal (2009)
This Master s Dissertation discusses the relation between cyberculture and subjectivity. Its main study objective is the identity projected in the Orkut profile, a virtual platform that enables the user to publicize his self in a social/community network of friends. The practice of building profiles that confer singularities and visibility to the subjectivities acting in cyberspace, establishing boundaries for who I am , is marked by the problem of articulation between representation and simulation, in the permeable interface between the real, the virtual and the hyper-real, and also involves concepts in crisis such as identity and subject. Starting from the discovery that cyberspace comprises new processes of subjectivation by engendering the virtualization and glocalization of existence, and that social networks, particularly Orkut, enable new forms of experimenting the dimensions of being and of relating to others, this study, insofar as it concerns the aforementioned problem, established the following questions: (1) Does the profile of an Orkut user correspond to his identity?, and (2) What are the implications of the congruence between profile, identity and subject in cyberculture? These questions led to the formulation of three hypotheses: (1) Orkut constitutes and interesting discursive space for the enunciation and circumscription of the self in informational flows; (2) in cyberspace, identities/profiles hold a status equivalent to the user s own body as a dynamic instrument of individuation; and (3) the daily experience in signic bodies leads to the dissolution of the concrete spaces of living and promotes the strategies of cybercultural management of existence, producing a direct impact on the physical and biological reality of the body and the territory. With the purpose of observing, describing and analyzing the strategies of construction and projection of identity in virtuality, of reflecting upon the congruence or superposition between identity, subject, and profile in the processes of hyper-spectacularization of the self, and of presenting the resulting cyberspatial management correlated to the invisible phenomenon of signic indexation of content identities, the terms of the commissioning and use of the free services rendered by Orkut, as well as pages for the registration, construction, maintenance and presentation of profiles and communities, were selected as the corpus of this work. The plan underpinning this research into post-modernism, into the semiotics of culture, into sociodromology and into cultural states, among other compatible theories, provided the theoretical and epistemiological references necessary for the analysis of the object (identity/profile), for checking the hypotheses, and for solving the research problem. The set of methodological strategies adopted during the process of this work also incorporated the netnographic method to guide the exploratory survey in the virtual environment, the collection and interpretation of data, the participatory observation and the realization of interviews. With these characteristics, which insert this Master s Dissertation, in an interdisciplinary manner, into the area of Communication, the aim is to contribute toward the development of studies on cyberculture in Brazil